Pembinaan Karakter MEMORI (Mental, Moral, Intelektual) pada Anak Jalanan di Kota Pangkalpinang - Rini Islamiati; Maya Yusnita (Universita Bangka Belitung, 2023)
Children should have the right and obligation to pursue education because children are the next generation of the nation who will face challenges and competition in the future. But for street children, education is not a priority because they spend most of their time on the streets. Even though they are on the streets all day long, street children should still be able to get an education. If they cannot attend formal education, at least they will get character education to shape theirpersonality to become good human beings. Because of the importance of character education for street children, the government has a responsibility to foster street children. Through this Humanitarian Program, street children in Pangkalpinang City are provided with facilities and education such as a character building program that aims to form good character. This humanitarian project program uses participatory mentoring methods in learning to read, draw, color, distribute blessings and creativity classes. The location taken for this humanitarian project program is in the center of Pangkal Pinang City in collaboration with related parties, namely the Office of Social Affairs and Labor Pangkalpinang City as an institution dealing with social problems. It is hoped that in the future this humanitarian project program will beable to become a motivator and shape the character of street children who are MEMORABLE (mental, moral andintellectual), and as an effort for the government, especially the Pangkalpinang City Social Service to reduce the number of street children in Pangkalpinang City.